Direct Method Solution of 3-D Magnetotelluric Modeling Using Vector Finite Element Method - Rudy Prihantoro; Doddy Sutarno; Nurhasan Nurhasan (Institute for Research and Community Services (LPPM) ITB, 2019)
As exploration is forced into more difficult areas with complex three-dimensional (3-D) structural environments, the importance of 3-D magnetotelluric (MT) modeling is essential for the correct interpretation of MT data. To reduce the complexity of the calculations introduced by 3-D models, iterative forward calculation of MT response functions is used as basis for inversion of 3-D MT data. This paper proposes an alternative procedure for making reliable 3-D MT modeling codes for forward calculation that is not only effective but also accurate. This is accomplished by using a direct method to solve the linear systems arising from the discretization process in the vector finite element approach. The vector finite element method is known for its capability of overcoming difficulties in modeling caused by possible jumps of normal components across discontinuities of material properties. Meanwhile, by using a direct method rather than an iterative method, the process of solving the linear equations does not suffer from slow convergence. Here, we present a comparison between our modeling codes and codes based on a different approach. In the resulting 3-D MT responses it was found that the proposed method has high accuracy.